ANALISIS KEBUTUHAN AIR BERSIH UNTUK PENGHUNI RUMAH SUSUN APARATUR SIPIL NEGARA RUMAH SAKIT BAHTERAMAS DI KOTA KENDARI - Yuni Ikasari Arif Ridangka; Romy Talanipa; Rini Sriyani (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2017)
Abstract The ASN apartment building Bahteramas Hospital in Kendari City was built on March 26 2018 which consists of 3 floors and has an area of ± 780,937 m2 of repairs. In order to support its capacity and function, the supply of water with good quality and quantity, the disposal of dirty water and rainwater that has no obstacles, and an adequate fire prevention system is absolutely necessary.This study aims to determine the amount of clean water needs by residents of the Bahteramas Hospital State Apparatus apartment in Kendari City which is calculated using three methods, namely based on the number of occupants, the type and number of plumbing devices, based on the load units of plumbing tools using prime data and secondary.The results of this study indicate that the need for clean water in the Flat Building of the State Civil Apparatus Bahteramas Hospital based on the number of occupants on average per day is 79,65 m3/day. Calculation of clean water needs based on the amount of plumbing equipment in a residential building using daily water is 776,9 m3/day. Calculation of clean water needs based on the unit load of plumbing equipment in a flat building using water for daily water use is 108,75 m3/day.  Abstrak Bangunan rumah susun ASN Rumah Sakit Bahteramas di Kota Kendari yang dibangun pada tanggal 26 maret 2018 yang terdiri dari 3 lantai dan mempunyai luas ± 780,937 m2  perlantainya. Demi mendukung kapasitas serta fungsinya, maka persediaan air dengan kualitas dan kuantitas yang baik, pembuangan air kotor dan air hujan yang tidak ada hambatan, serta sistem pencegah kebakaran yang memadai mutlak di perlukan.Penelitian ini bertujuan untuk mengetahui jumlah kebutuhan air bersih yang diperlukan penghuni rumah susun Aparatur Sipil Negara Rumah Sakit Bahteramas di Kota Kendari yang dihitung dengan menggunakan tiga metode yaitu berdasarkan jumlah penghuni, jenis dan jumlah alat plumbing, berdasarkan unit beban alat plumbing dengan menggunakan data prime dan sekunder.Hasil penelitian ini menunjukkan bahwa kebutuhan air bersih pada Gedung Rumah Susun Aparatur Sipil Negara Rumah Sakit Bahteramas berdasarkan jumlah penghuni rata-rata perhari sebesar 79,65 m3/hari. Perhitungan kebutuhan air bersih berdasarkan jumlah alat plumbing pada gedung rumah susun pemakaian air perhari sebesar 776,9 m3/hari. Peritungan kebutuhan air bersih berdasarkan unit beban alat plumbing pada  gedung  rumah  susun  pemakaian  air  pada  pemakaian  air  perhari sebesar 108,75 m3/hari.